Evaluación Presupuestaria al Gobierno Autónomo Descentralizado Parroquial Rural de Triunfo Dorado, Cantón Centinela del Cóndor, periodo 2021-2022. - Guamán Camacho, Guisela Esperanza (2024)
The work of curricular integration entitled, "Budget Evaluation to the Decentralized Rural Parish Autonomous Government of Triunfo Dorado, Centinela del Condor Canton, period 2021-2022", was carried out with the purpose of developing the budgetary evaluation in order to measure the management carried out through the application of budgetary indicators. To achieve the research objectives, a methodology was applied based on the following steps: Request input from the institution to compare and analyze the information in detail and determine variations; then, the performance of the planned projects was evaluated; after that, indicators were applied to the different budget lines; finally, the information was consolidated in a budget evaluation report with the content of the results obtained, the same ones that show that the budget of the projects that are included in the Annual Operational Plan is not met 100%; thus by 2021, the accomplishment of income compared to those programmed represented 75,39% and by 2022 reached 72,84%, so according to the measurement standards, both periods are at a good level of accomplishment of this concept. For its part, the budget execution of expenditure for the year 2021 was 61,18%, so it is considered as a good level of implementation; in contrast, in 2022, 53,96% was obtained, being below the standard of measurement, demonstrating that the resources allocated are not used to carry out the planned works, so there were constant reforms due to the lack of a participatory budget that considers the needs of the communities. Also, it was determined that the institution had financial dependence on the government of 92,54%, considered an excellent level in 2021, while by 2022 it decreased to 77,72%, considered as good; therefore, it is important for rural governments to get support from the institutions that have the most resources so they can continue working to make the parish thrive. Finally, the institution had a financial solvency in the first period of 110,92% classified as excellent and in the second period of 85,93% what is considered as very good, indicating that the Rural Parish GAD of Triunfo Dorado reached an optimal level, as their current income covers current expenditure, which is stated in the respective report, recommending to the administration the adoption of improvement decisions.